Poetry RX : how fifty inspiring poems can heal and bring joy to your life - Rosenthal, Norman E. (Gildan Media LLC, aka G & D Media, 2021)
Rosenthal examines a selection of poems by various authors, analyzing the poetic forms, discussing the emotions evoked, and explaining the science behind the reactions. In doing this, he shows us how poetry has the power to help us understand ourselves.